Authenticity of Narrative Text Models Used in Junior High School Textbooks - Agung Hariyadi (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2018)
This present research focuses on two purposes: they are to find out the application of Vladimir Propp’s theory on narrative text models used in Junior High School Textbooks and the authenticity of narrative text models used in Junior high school textbooks. To answer the first research question, the theory is used to analyze the data through document analysis and the second research question answered by comparing the analyses of the text models of JHS textbooks and the authentic texts. The data were four narrative text models taken from four junior high school textbooks that contain narrative texts and the storybook as an example of authentic text. The result showed that the theory was generally applicated on narrative text models used in Junior High School and all of them are belong to not authentic. Three of them are the simplification of the authentic texts and the other is created text. This was caused by context of used (classroom), cultural context and students level of knowledge